Pap smear and colposcopy findings in female inmates of a prison unit in the state of São Paulo, Brazil - de Andrade, Fernando Moreira; de Amorim Andrade, Soraya Gomes; Araujo Júnior, Edward; Campaner, Adriana Bittencourt; da Silva, Maria Antonieta Longo Galvão; Fernandes, Gustavo Leme; Aldrighi, José Mendes (Ceska gynekologie, 2024)
OBJECTIVE: The objective of this study was to evaluate the Pap smear and colposcopy findings in female inmates in a prison unit in the state of São Paulo, Brazil. METHODS: A retrospective cross-sectional study was carried out by analyzing the Pap smear and colposcopy examinations of female inmates in a prison unit. The following socio-demographic data were assessed: age, nationality, level of education, marital status, height, weight, ethnicity, occupation, religion, sexual orientation, and presence of tattoos. RESULTS: The sample consisted of 894 women who had a Pap smear, the majority of whom were Brazilian (93.6%), 41.1% had an incomplete primary education, 58.5% were single, 50.1% were white, 60.7% had tattoos, and the predominant religion was Catholicism at 42.8%. Regarding sexual orientation, 124 (13.9%) women identified as bisexual, 640 (71.6%) as heterosexual, and 127 (14.2%) as homosexual. Most Pap smears showed benign findings (86.5%). Of the female inmates who had a Pap smear, 121 (13.5%) were referred for colposcopy. Altered colposcopy findings occurred in 95 (10.6%), with the most common findings being high-grade squamous intraepithelial lesions 36 (4.0%) and low-grade squamous intraepithelial lesions 27 (3.0%). The majority of women (96.0%) had no clinical signs of human papillomavirus - HPV (anogenital verrucous lesions) and only 36 (4.0%) had lesions suggestive of HPV on Pap smears. There were more HIV cases in the group with HPV verrucous lesions (P = 0.013). CONCLUSION: We observed 13.5% and 78.5% of abnormal findings in Pap smears and colposcopy, resp.), in female inmates in a prison unit in the state of São Paulo, Brazil.
Keywords: dospělí; vězni; Female; Papanicolaouův test; Adult; mladý dospělý; ženské pohlaví; průřezové studie; Brazil; Adolescent; Pap smear; Prisoners; lidé; prison; nádory děložního čípku; Papanicolaou Test; female inmates; retrospektivní studie; Cross-Sectional Studies; Young Adult; colposcopy; Vaginal Smears; Brazílie; Colposcopy; Uterine Cervical Neoplasms; kolposkopie; vaginální stěr; lidé středního věku; Uterine Cervical Dysplasia; HPV; Retrospective Studies; Middle Aged; mladiství; dysplazie děložního hrdla; Humans